Legal Protection For Key Witnesses In Handling Police Murder Cases In The Police Institution Of The Republic Of Indonesia (Case Study Of The Murder Of Brigadier Nofriansyah Joshua Hutabarat) - Umar Anwar; Muhammad Nur Islami; Markus Marselinus Soge; Budi Priyatmono (Polteknik Ilmu Pemasyarakatan, 2023)
The emergence of the murder case of Brigadier Nofriansyah Joshua Hutabarat or Brigadier J exposed the mafia in the National Police Agency whose name was Inspector General Ferdy Sambo as the main perpetrator. This condition stems from the key witness Bar Richard Eliezer Pudihang Lumiu or Bharada E who uncovered all these cases and other names. This became a big problem for Bharada E because of the threat to his security as a key witness in the murder incident. It is important to carry out this research in order to determine the legal protection of key witnesses in uncovering the case of Brigadier J's murder. The research method used is a case study and normative juridical. The result of the analysis is that legal protection for key witnesses must be carried out by the state. The Witness and CVictim Protection Agency (LPSK) provides special protection to key witnesses in maintaining the security of themselves, their families and those who are close to key witnesses. The conclusion is the key that must be protected in dismantling and maintaining the safety of himself and his family.